Structural properties of Mg - x wt% Co (x = 0, 5, 10 & 20) nanocomposites for hydrogen storage applications. (2021) - Rattan Paul, Devina; Sharma, Rishabh; Sharma, Anshu; Panchal, Priyanka; Singh, Anita; Chaudhary, Sudesh; Nehra, S.P.
Abstract: This work represents the hydrogen storage possibilities in Magnesium (Mg)-based nanocomposites. Mg materials are abundant in nature and are of interest as hydrogen storage material due to their cost effectiveness and better hydrogen storage capacity. But, in Mg hydrides strong metal-hydrogen bond results very slow dehydrogenation process, that hinder its application for onboard storage. Effect of the cobalt on ball-milled Mg with different wt% is studied in atmospheric condition. Pristine Mg was ball milled for 12 h and after addition of Co the mixture was ball milled for further 2 h. X‐ray Diffraction (XRD) technique was employed for structural analysis. Field Emission Scanning Electron Microscope and energy-dispersive X-ray spectroscopy (EDXS) were employed to analyze the particle morphology, distribution and elemental analysis of the Mg - x wt% Co (x = 0, 5, 10 & 20) nanocomposites respectively.